Splenic B cells are required for tolerogenic antigen presentation in the induction of anterior chamber-associated immune deviation (ACAID). - D'Orazio, T J (1998)
Ocular immune privilege is the result of a number of protective mechanisms, including a specialized immune response to antigen encountered in the anterior chamber of the eye. Anterior chamber-associated immune deviation, or ACAID, is characterized by the antigen-specific, selective down-regulation of systemic cell-mediated and humoral immune responses. One current hypothesis of the initiation of ACAID predicts that ocular APC process antigen and then migrate out of the eye and to the spleen where various regulatory T-cell populations are generated. A novel in vitro model of the ACAID spleen was developed to study the cells involved in the generation of suppressed T-cell immunity. ACAID APC co-cultured with whole splenocytes or splenic B and T cells induced efferent suppressors of delayed-type hypersensitivity (DTH). However, ACAID APC co-cultured with splenic T cells did not generate efferent suppressors of DTH. The requirement for B cells was confirmed with B-cell knockout mice. ACAID APC co-cultured with splenocytes from B-cell knockout mice did not induce efferent suppressors of DTH. Moreover, ACAID could not be induced in B-cell knockout mice in vivo. The reconstitution of B-cell knockout mice with wild-type B cells restored ACAID. In summary, these data confirm the role for B cells in the splenic phase of ACAID. A putative mechanism predicts that ACAID APC release antigenic peptides to B cells in the spleen. B cells then present antigen in a tolerogenic manner leading to the generation of regulatory T cells.